Development of Entrepreneurial Skills on the Basis of Innovative Technologies - Zukhra Karabayevna Ismailova; Mukhaye Khudaiberganovna Baybaeva; Inomiddin Abdulkhamidovich Imomov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article notes that the quality of education in developed countries is determined by the level of initiative of the staff, the level of development of its innovative and creative activity, the practice of developing entrepreneurial abilities of students based on socio-psychological trainings, business games, television shows, debates in South Korea, China is also widespread. Russia, Germany and France, including reforms in the education system, are focused on issues of developing entrepreneurship in the future, improving mechanisms for their development creativity.Along with the foregoing, the article focuses on the sociological and anthropological components and ethno-regional factors of entrepreneurship development, the national mentality and principles of social partnership as a result of global research on entrepreneurship development.